Respuesta :
You need to plug in -18 into the equation. So h(-18)=17+(-18)/6
h(-18)=17-3
h(-18)=14
h(-18)=17-3
h(-18)=14
Answer: [tex]h(-18)=14[/tex]
Step-by-step explanation:
We are given a function : [tex]h(x)=17+\dfrac{x}{6}[/tex]
To find the value of [tex]h(-18)[/tex] , we need to substitute the value of x = -18 in the given function h(x).
Thus, substitute x= -18 in the given function h(x), we get
[tex]h(-18)=17+\dfrac{(-18)}{6}\\\\\Rightarrow\ h(-18)=17-3[/tex] (product of a negative and positive sign is negative)
[tex]\Rightarrow\ h(-18)=14[/tex]
Hence, the value of [tex]h(-18)=14[/tex]